EVALUASI PENYELENGGARAAN BLENDED LEARNING PENDIDIKAN DAN PELATIHAN DASAR PENGAWAS KETENAGAKERJAAN PADA PUSAT PENGEMBANGAN SUMBER DAYA MANUSIA KETENAGAKERJAAN - Niki Ferdian; Amy Yayuk Sri Rahayu (LPSDI Bina Patria, 2022)
This istudy iaims ito analyze tthe dependent variable of the icurrent iaccount balance in iASEAN-6 by sampling based on annual time-series data for the 2010-2019 period. The independent ivariables iused iin ithis istudy iare ithe exchange rate as the core independent variable, then igross idomestic iproduct iand iforeign idirect iinvestment as control ivariables. All idata iin ithis istudy iwere iobtained ifrom ithe World Bank. Fixed effect model (FEM) panel data analysis method was used. Based ion ithe ipartial itest (t-test), ithe core independent variable of the exchange rate ihas ia isignificanti effect ion ithe icurrent iaccount balance in ASEAN-6, as well as the control variable, namely gross domestic product and foreign direct investment, which has a significant effect on the current account balance in ASEAN-6. Meanwhile, tthe isimultaneous itest (F-Test) shows ithat ithe iexchange irate, igross idomestic product iand iforeign idirect iinvestment simultaneously ihave ia isignificant ieffect ion ithe current iaccount ibalance iin ASEAN-6.